"All-in-Gel" design for supercapacitors towards solid-state energy devices with thermal and mechanical compliance. Issue 15 (1st April 2019) - Yin, Chengyao; Liu, Xinhua; Wei, Junjie; Tan, Rui; Zhou, Jie; Ouyang, Mengzheng; Wang, Huizhi; Cooper, Samuel J.; Wu, Billy; George, Chandramohan; Wang, Qigang
Abstract : "All-in-gel" supercapacitor is designed via ionogel composite electrolyte and Bucky gel electrodes. These flexible, conductive and shape-conformable gels represent a step change in the design of safe energy storage devices for wearable electronics, in particular those facing the increased demands of hazardous operational environments. Abstract : Ionogels are semi-solid, ion conductive and mechanically compliant materials that hold promise for flexible, shape-conformable and all-solid-state energy storage devices. However, identifying facile routes for manufacturing ionogels into devices with highly resilient electrode/electrolyte interfaces remains a challenge. Here we present a novel all-in-gel supercapacitor consisting of an ionogel composite electrolyte and bucky gel electrodes processed using a one-step method. Compared with the mechanical properties and ionic conductivities of pure ionogels, our composite ionogels offer enhanced self-recovery (retaining 78% of mechanical robustness after 300 cycles at 60% strain) and a high ionic conductivity of 8.7 mS cm −1, which is attributed to the robust amorphous polymer phase that enables facile permeation of ionic liquids, facilitating effective diffusion of charge carriers. We show that development of a supercapacitor with these gel electrodes and electrolytes significantly improves the interfacial contact between electrodes and electrolyte, yielding an area specific capacitance of 43 mF cm −2 at a current density of 1.0 mA cm −2 . Additionally, through this all-in-gel design a supercapacitor can achieve a capacitance between 22–81 mF cm −2 over a wide operating temperature range of −40 °C to 100 °C at a current density of 0.2 mA cm −2 .